PENGARUH KEPEMIMPINAN DAN KOMPETENSI SDM TERHADAP KINERJA PEGAWAI INSPEKTORAT JENDERAL KEMENTERIAN PENDIDIKAN DAN KEBUDAYAAN JAKARTA - Raisid, Izhar Aduardo; Lestari, Hesti; Rostyaningsih, Dewi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
This research entitled â€œAnalysis of The Effect of Leadership and Competence of Human Resources on Employees Job Performance in Inspektorat Jenderal Kementerian Pendidikan dan Kebudayaanâ€. This research is based on fact that employees job performance in Inspektorat Jenderal Kementerian Pendidikan dan Kepegawaian have several problems such as late for attendance, procrastination completion of the work, and the other factors. The purpose of this research is to find out the effect of leadership and competence of human resources in Inspektorat Jenderal Kementerian Pendidikan dan Kebudayaan. Employee job performance is the result of an employee in a particular period. Employee job performance is influenced by several factors such as individual factors, leadership factors, team factors, and system factors. This research is focusing on individual factor that include competence of human resources and leadership factor that include leadership that applied by the leader. This research methodology uses a quantitative approach. The research sample is amount 100 respondents. Method of collecting data in this research by using a questionnaire given to the entire sample in this research. This questionnaire using likert-type scale and through the stages of validity, reliability test, cross tabulation analysis, correlation analysis kendall, coefficient determination test, and kendall concordance test as data processing method. Based on this research, leadership and competence of human resources have an effect on employee job performance in Inspektorat Jenderal Kementerian Pendidikan dan Kebudayaan. This results is proved by coefficient determination test that shows leadership and competence of human resources have an effect ammount 47,20% on employee job performance. However, there are several indivators of leadership and competence of human resourch need to be improved to increase the performance of both the leadership and employees.